Elements of Semiotics - Lidov, David (New York St. Martin's Press, 1999)
Conventionally, one says that semiotics is the study of signs, and that a sign is something that stands for something else. These definitions are scant clues to the origins and motivations of semiotics as a characteristic intellectual movement of the 20th century. Elements of Semiotics offers a unified foundation for semiotics understood as a comparative perspective of the artifacts of mental life. It is arranged to be useful to the novice, presenting a new theory in the context of classical sources and identifying signs with consciousness. David Lidov establishes a sub-study of comparative articulation which builds on the work of Hjelmslev, Martinet, Goodman, and Troubetskoy. His concept of the "elaborated sign" allows a reconciliation of structural and pragmatistic insights, in which the observation that structure and reference may develop antithetically is a key principle.
Keywords: Semiotics